Peritoneal dialysisrelated peritonitis with an unexpected micro-organism: enterococcus hirae - Dilek Barutcu Atas; Basar Aykent; Ebru Asicioglu; Hakki Arikan,Arzu Velioglu; Serhan Tuglular; Cetin Ozener (Medicine Science, 2017)
Enterococcus Hirae is a gram-positive, facultative, anaerobic bacteria which is usually a zoonotic pathogen rarely isolated from human infections. There are no published reports describing continuous ambulatory peritoneal dialysis (CAPD) related- peritonitis with Enterococus Hirae in the literature. With the following report, we describe the case of peritoneal dialysis (PD)-related peritonitis due to Enterococcus Hirae. [Med-Science 2017; 6(1.000): 120-1]